2018
DOI: 10.1149/2.0571803jes
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Rate-Limiting Factors in Thick Electrodes for Electric Vehicle Applications

Abstract: Increasing electrode thickness and loading can help Li-ion batteries achieve higher energy densities, but the resulting decay in electrochemical performance at elevated rates remains a significant challenge. In order to design an optimal thick electrode, understanding how performance loss occurs is necessary. While it is known that both ionic and electronic conductivity contribute to rate performance, we observed a stronger correlation between electronic conductivity and electrochemical performance of electrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 82 publications
(69 citation statements)
references
References 40 publications
1
68
0
Order By: Relevance
“…For the first time, stochastic microstructure modeling and 3D microstructure resolved simulations of ultra‐thick electrodes were used to correlate electrochemical (EC) data to different microstructural scenarios. The simulations were used to analyze the effect of the CBD distribution and morphology on electrode performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the first time, stochastic microstructure modeling and 3D microstructure resolved simulations of ultra‐thick electrodes were used to correlate electrochemical (EC) data to different microstructural scenarios. The simulations were used to analyze the effect of the CBD distribution and morphology on electrode performance.…”
Section: Discussionmentioning
confidence: 99%
“…Patry et al evaluated the impact of electrode coating thickness on the cell cost for different cathode active materials (AMs) and found that the doubling of the electrode thickness from 50 to 100 μm for NCM 111 (Li(Ni 1/3 Co 1/3 Mn 1/3 )O 2 ) leads to a potential cost reduction of 24% per kilowatt hour ($ kW h −1 ) . Therefore, the concept of thick electrodes was recently investigated experimentally by several groups, yielding electrodes with high mass loadings, for example, coated on porous metal current collectors or produced binder‐free by Templating or Spark Plasma Sintering (SPS) and studied by modeling and simulation …”
Section: Introductionmentioning
confidence: 99%
“…The electrodes were fabricated by casting the slurry of active materials (U-LTO-NHMS and LiNi 0.5 Mn 1.5 O 4 ), Super-P, and poly (vinylidene fluoride) (PVDF) binder with a mass ratio of 7:2:1 in N-methyl-2-pyrrolidone (NMP) solvent on Al or Cu foil, and then dried at 120 C for 8 h in a vacuum oven before use [40]. Type CR-2032 coin cells were assembled to evaluate the electrochemical properties of all the samples.…”
Section: Electrochemical Measurementmentioning
confidence: 99%
“…Research therefore focuses on the structuring of electrodes, e.g., by laser post‐processing steps or by new processing methods to provide pathways from the electrode surface to the substrate for faster Li‐ion transport . Though a broad knowledge base about transport limitations and tailoring of electrode porosity exists, the significant influence of the electrode production process, namely speaking of the coating and drying conditions on electrode microstructure and cell performance, is often not considered …”
Section: Introductionmentioning
confidence: 99%